The Moralist International Russia in the Global Culture Wars - Stoeckl, Kristina (Orthodox Christianity and Contemporary Thought, 2022)
p emThe Moralist International/em analyzes the role of the Russian Orthodox Church and the Russian state in the global culture wars over gender and reproductive rights and religious freedom. It shows how the Russian Orthodox Church in the past thirty years first acquired knowledge about the dynamics, issues, and strategies of Right- Wing Christian groups; how the Moscow Patriarchate has shaped its traditionalist agenda accordingly; and how the close alliance between church and state has turned Russia into a norm entrepreneur for international moral conservativism. Including detailed case studies of the World Congress of Families, anti-abortion activism, and the global homeschooling movement, the book identifies the key factors, causes, and actors of this process. Kristina Stoeckl and Dmitry Uzlaner then develop the concept of conservative aggiornamento to describe Russian traditionalism as the result of conservative religious modernization and the globalization of Christian social conservatism. emThe Moralist International/em continues a line of research on the globalization of the culture wars that challenges the widespread perception that it is only progressive actors who use the international human rights regime to achieve their goals by demonstrating that conservative actors do the same. The book offers a new, original perspective that firmly embeds the conservative turn of post-Soviet Russia in the transnational dynamics of the global culture wars. The Moralist International emis available from the publisher on an open-access basis./em /p